Small Cell Undifferentiated Histology Does Not Adversely Affect Outcome in Hepatoblastoma: A Report From the Children's Oncology Group (COG) AHEP0731 Study Committee. Issue 5 (10th February 2022) - Trobaugh-Lotrario, Angela; Katzenstein, Howard M.; Ranganathan, Sarangarajan; Lopez-Terrada, Dolores; Krailo, Mark D.; Piao, Jin; Chung, Nadia; Randazzo, Jessica; Malogolowkin, Marcio H.; Furman, Wayne L.; McCarville, Elizabeth B.; Towbin, Alexander J.; et al.
Abstract : PURPOSE: Small cell undifferentiated (SCU) histology in hepatoblastoma (HB) tumors has historically been associated with a poor prognosis. Tumors from patients enrolled on Children's Oncology Group (COG) study AHEP0731 underwent institutional and central pathologic review for identification of SCU histology. PATIENTS AND METHODS: Patients with SCU histology identified at the local treating institution who had otherwise low-risk tumors were upstaged to the intermediate-risk treatment stratum, whereas those only identified by retrospective central review were treated per the local institution as low-risk. Patients with otherwise intermediate- or high-risk tumors remained in that treatment stratum, respectively. Central review was to be performed for all tissue samples obtained at any time point. Treatment was per local review, whereas analysis of outcome was based on central review. RESULTS: Thirty-five patients had some elements (1%-25%) of SCU identified on central review of diagnostic specimens. All but two patient tissue sample retained nuclear INI1 expression. The presence of SCU histology did not correlate with age, alpha-fetoprotein level at diagnosis, or sex. The presence of SCU did not affect event-free survival (EFS). EFS at 5 years for patients with low-risk, intermediate-risk, and high-risk with SCU HB was 86% (95% CI, 33 to 98), 81% (95% CI, 57 to 92), and 29% (95% CI, 4 to 61), respectively, compared with EFS at 5 years for patients without SCU enrolled with low-risk, intermediate-risk, and high-risk of 87% (95% CI, 72 to 95), 88% (95% CI, 79 to 94), and 55% (95% CI, 32 to 74; P = .17), respectively. CONCLUSION: The presence of SCU histology in HB does not appear to adversely affect outcome. Future studies should be able to treat patients with SCU HB according to risk stratification without regard to the presence of SCU histology.